Pengaruh Penggunaan Metode Index Card Match terhadap Keaktifan Belajar PAI Siswa SDIT Juara Padang Panjang - Febby Febby; Arifmiboy Arifmiboy; Darul Ilmi; Hamdi Abdul Karim (Universitas Palan, 2024)
The low level of PAI learning activity among students is the driving force for this study. It is believed that the use of learning techniques is inextricably linked to this low activity in PAI learning. Index Card Match is one of the instructional strategies that is thought to have an impact on students' learning activities. to determine if there is a noteworthy impact on Index Card Match use. In order to go toward active learning, the author must carry out experimental study. The Quasy Experiment Design approach was used as the research method in this quantitative study. The location of this study is SDIT Juara Padang Panjang. Class IV A, IV B, and IV C, which were selected at random from 76 students' PTS scores, made up the study's population. Class IV A served as the experimental class and Class IV B as the control class. A questionnaire was one of the research tools utilized in this study (questionnaire). The t-test and F-test were used in the analytical process. The f-test was employed in the experimental class and the t-test in the control class to analyze the data. Based on the data processing results, the study findings indicate that there is a substantial difference in the usage of the Index Card Match technique on students' active PAI learning, supporting the first hypothesis. The fact that tcount (2,560) is higher than ttable (1,677) indicates this. Furthermore, it is evident that there is a considerable impact since the second hypothesis, Fcount, is 96.057 at a significance level of 0.010 <0.05, leading to the rejection of Ho and the acceptance of Ha. Thus, it can be said that using the Index Card Match Method has a big impact on active PAI learning.